1995
DOI: 10.1128/jcm.33.4.978-981.1995
|View full text |Cite
|
Sign up to set email alerts
|

Controlled evaluation of BacT/Alert standard aerobic and FAN aerobic blood culture bottles for detection of bacteremia and fungemia

Abstract: A new medium, FAN, designed to enhance the recovery of microorganisms, has been developed for the BacT/Alert blood culture system (Organon Teknika Corp., Durham, N.C.). We compared the yield and speed of detection of microorganisms in 6,847 adequately filled paired aerobic standard and FAN bottles at four university hospitals. Of 499 clinically significant microorganisms isolated from one or both bottles, significantly more Staphylococcus aureus isolates (P < 0.001), coagulase-negative staphylococci (P < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 13 publications
6
54
1
3
Order By: Relevance
“…In the vast majority of institutions, most blood culture specimens delivered to the laboratory are entered into an incubation protocol on a continuously monitored blood culture device. There are several manufacturers of such devices, and their performance characteristics are similar [27][28][29][30][31][32][33][34][35]. These devices incubate the blood culture bottles for a prescribed period of time (determined by the user) and signal audibly and/or visually if growth is detected.…”
Section: Laboratory Techniques For Blood Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In the vast majority of institutions, most blood culture specimens delivered to the laboratory are entered into an incubation protocol on a continuously monitored blood culture device. There are several manufacturers of such devices, and their performance characteristics are similar [27][28][29][30][31][32][33][34][35]. These devices incubate the blood culture bottles for a prescribed period of time (determined by the user) and signal audibly and/or visually if growth is detected.…”
Section: Laboratory Techniques For Blood Culturementioning
confidence: 99%
“…Medium combinations typically include aerobic and anaerobic formulations and, in select circumstances, a formulation containing reagents that are ideal for recovering mycobacteria and/or yeasts may be inoculated as well. Controlled studies comparing the performance of media with and without the addition of antimicrobial binding or absorbing agents (resins and/or charcoal compounds) have repeatedly demonstrated that the latter formulations are clearly superior for the recovery of microorganisms, especially staphylococci and yeasts [29,[34][35][36][37].…”
Section: Laboratory Techniques For Blood Culturementioning
confidence: 99%
“…Others demonstrated that the use of bottles with antibiotic-neutralizing ingredients allow growth of microorganisms in CB that would not occur with conventional media such as P. acnes. 7,37,38 Recently, Akel and colleagues described a clever validation approach fulfilling regulatory requirements regarding CB sterility using BACTEC Plus medium. This medium contains resin-neutralizing antibiotics, which were present in as much as 30% of their CB units.…”
Section: Discussionmentioning
confidence: 99%
“…The length of hospital stay (LOS) was taken as the duration between the date of admission and the day the blood culture was detected as positive. Infections that occurred after 72 hours of hospital admittance were considered as nosocomial infections in accordance with the studies conducted by Weinstein et al [12] and Laupland and Church [13].…”
Section: Determining Length Of Hospital Staymentioning
confidence: 99%
“…Age was categorized based on the United Nations Provisional Guidelines, 1982 [14]. Accordingly, age groups were included in the study were Infants (0-1 year), Pre-school (2-5 years), Schooling (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), Working (20-60 years) and Seniors (>60 years). The overall study population consisted of 104 (49.5%) paediatric patients of which 53 (25.2%) had bacteraemia and a total of 106 (50.5%) adult patients of which 67 (31.9%) had bacteraemia.…”
Section: Study Population and Demographic Characteristicsmentioning
confidence: 99%